Comparative study and simulation of tumor cell inactivation by microwave and conventional heating - Rosin, Andreas; Hader, Michael; Drescher, Corinna; Suntinger, Magdalena; Gerdes, Thorsten; Willert-Porada, Monika; Gaipl, Udo; Frey, Benjamin (Compel-The International Journal For Computation and Mathematics in Electrical and Electronic Engineering, 2018)
Purpose This paper aims to investigate in a self-designed closed loop reactor process conditions for thermal inactivation of B16 melanoma cells by microwave and conventional heating. Design/methodology/approach Besides control experiments (37 degrees C), inactivation rate was determined in the range from 42 degrees C to 46 degrees C. Heating was achieved either by microwave radiation at 2.45 GHz or by warm water. To distinguish viable from dead cells, AnnexinV staining method was used and supported by field effect scanning electron microscopy (FE-SEM) imaging. Furthermore, numerical simulations were done to get a closer look into both heating devices. To investigate the thermal influence on cell inactivation and the differences between heating methods, a reaction kinetics approach was added as well. Findings Control experiments and heating at 42 degrees C resulted in low inactivation rates. Inactivation rate at 44 degrees C remained below 12% under conventional, whereas it increased to >70% under microwave heating. At 46 degrees C, inactivation rate attained 68% under conventional heating; meanwhile, even 88% were determined under microwave heating. FE-SEM images showed a porous membrane structure under microwave heating in contrast to mostly intact conventional heated cells. Numerical simulations of both heating devices and a macroscopic Arrhenius approach could not sufficiently explain the observed differences in inactivation. Originality/value A combination of thermal and electrical effects owing to microwave heating results in higher inactivation rates than conventional heating achieves. Nevertheless, it was not possible to determine the exact mechanisms of inactivation under microwave radiation.
EVALuna2:36524